2012
DOI: 10.1039/c1cs15171a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemistry: opportunities for new and cleaner synthesis

Abstract: Citation for published item:tmesD F vF nd edmsD gF tF nd folmD gF nd frgD hF nd gollierD F nd pri § s § i¡ D F nd qrepioniD pF nd rrrisD uF hF wF nd ryettD qF nd tonesD F nd uresD eF nd wkD tF nd winiD vF nd yrpenD eF qF nd rkinD sF F nd herouseD F gF nd teedD tF F nd ddellD hF gF @PHIPA 9wehnohemistry X opportunities for new nd lener synthesisF9D ghemil soiety reviewsFD RI @IAF ppF RIQERRUF Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
1,672
0
19

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 2,509 publications
(1,771 citation statements)
references
References 398 publications
9
1,672
0
19
Order By: Relevance
“…The incident energy and detector distance (1,225.76 mm) were calibrated using a NIST CeO 2 standard sample and the Fit2D software package (ESRF Internal Report, ESRF98HA01T, FIT2D V9.129 Reference Manual V3. 1,1998). Raw data frames were integrated using Fit2D.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incident energy and detector distance (1,225.76 mm) were calibrated using a NIST CeO 2 standard sample and the Fit2D software package (ESRF Internal Report, ESRF98HA01T, FIT2D V9.129 Reference Manual V3. 1,1998). Raw data frames were integrated using Fit2D.…”
Section: Methodsmentioning
confidence: 99%
“…M echanochemical reactions by milling or grinding have emerged as excellent, rapid and cleaner alternatives to conventional chemical synthesis in a number of areas, from nanomaterials and alloys to pharmaceuticals and metal-organic frameworks [1][2][3][4] . However, despite significant and rapid advances in synthetic scope and methoodology [5][6][7] , the mechanistic understanding of mechanochemical reactions has remained elusive [8][9][10] , creating a major obstacle for the development and optimization of attractive proof-of-principle laboratory experiments into viable large scale processes 11 .…”
mentioning
confidence: 99%
“…2, Co and Li could be leached out to a certain degree from LiCoO 2 after co-grinded with different additives, indicating that Co and Li inside LiCoO 2 powder were tentatively converted into their chloride forms during mechanochemical process. It has been reported that mechanical forces such as shear, impact and squeezing exerted by ball milling, will transmit energy to powder, diminished powder particles and destroy the crystal structures (James et al, 2012;Nasser and Mingelgrin, 2012). Moreover, the ball milling process can reduce specific surface energy of reaction products so as to promote the impossible solid-solid reaction and enhance the reaction efficiency (Friščić , 2010).…”
Section: Screening Of Co-grinding Reagentsmentioning
confidence: 99%
“…[1][2][3][4][5] Avoiding toxic solvents not only decreases potential hazards, but can also reduce the overall cost of a process. 5 A variety of materials and compounds have been prepared mechanochemically including metal alloys, 6 metal organic frameworks (MOFs), 7 and organic compounds from reactions such as the Knoevenagel condensation [8][9][10] and Wittig reaction, 11 amongst others. 12 However, two main drawbacks of mechanochemical synthesis are the general lack of both temperature control and scalability.…”
Section: Introductionmentioning
confidence: 99%